Association between vitamin D receptor BsmI polymorphism and bone mineral density in pediatric patients: A meta-analysis and systematic review of observational studies. Issue 17 (April 2017) - Bao, Li; Chen, Mingzhi; Lei, Yong; Zhou, Zemin; Shen, Huiping; Le, Feng
Abstract: Background: Vitamin D and the vitamin D receptor (VDR) are important in the metabolic processes that affect bone mineral density (BMD). However, the effect of VDR BsmI polymorphism on BMD in pediatric patients is still unclear. Methods: Eligible studies were identified from the following electronic databases: PubMed, Embase, the Cochrane Library, and the Chinese CNKI and Wanfang databases before October 1, 2016. Data were extracted from the eligible studies, and associations between VDR BsmI polymorphism and BMD in pediatric patients were estimated with weighted mean differences (WMDs) and 95% confidence intervals (CIs). Subgroup analysis of ethnicity and sensitivity analyses were used to identify sources of heterogeneity. Results: A significant difference was observed between VDR BsmI polymorphism and pediatric BMD levels of the lumbar spine (LS) in the corecessive model (bb vs BB + Bb: WMD = −0.23, 95% CI [−0.35, −0.11], P  < 0.01). No significant relationship was found in the dominant, recessive, or codominant models for LS BMD (BB vs Bb: WMD = −0.56, 95% CI [−1.58, 0.46], P  = 0.29; BB vs bb: WMD = −0.54, 95% CI [−1.49, 0.41], P  = 0.27; and BB vs Bb + bb: WMD = −0.45, 95% CI [−1.71, 0.26], P  = 0.22). In addition, we found no remarkable association between the BsmI polymorphism and BMD levels of the femoral neck (FN) in children (BB vs Bb: WMD = −1.08, 95% CI [−3.13, 0.96], P  = 0.30; BB vs bb: WMD = 0.98, 95% CI [−0.89, 2.85], P  = 0.31; BB vs Bb + bb: WMD = −0.061, 95% CI [−0.30, 0.17], P  = 0.61; and bb vs BB + Bb: WMD = 0.82, 95% CI [−0.59, 2.32], P  = 0.25). Conclusion: Our meta-analysis found that the VDR BsmI genetic polymorphism was correlated with LS BMD level in pediatric patients: compared with those with the B allele, children with the bb genotype were less likely to have lower BMD levels. No significant difference was identified in the pediatric FN BMD levels.